The contribution of price and pharmacy location to loyalty: Mediated by satisfaction and patronage in retail pharmacy - Glenn Cahya Dwi Ramadhan; Tengku Ezni Balqiah (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2025)
This study aims to examine the influence of perceived service quality, perceived price competitiveness, and store location on customer loyalty intentions in pharmacies, considering customer satisfaction and patronage as mediators. This research employs a quantitative approach, surveying pharmacy consumers in Indonesia. The Structural Equation Modeling (SEM) is utilized to analyze the data and test the relationships between variables. The findings suggest that perceived price competitiveness and store location have a significant impact on both customer satisfaction and loyalty intentions. Meanwhile, perceived service quality directly influences satisfaction but does not directly affect loyalty intention. Neither patronage towards the rated pharmacy nor other pharmacies (disloyalty) shows significant effects on customer loyalty. This study offers insights into the factors that influence customer loyalty in the Indonesian pharmacy sector, a developing market. It reveals that besides service quality, price and location factors play crucial roles in shaping customer satisfaction and loyalty, offering new perspectives for stakeholders to design more effective marketing strategies.